Properties of Thin Film Composites of rGO–SnO2 and Modeling of Ultraviolet Laser-Induced Conductivity Decay - de Almeida, André Luis [UNESP]; Fonseca, Lucas Prado [UNESP]; de Oliveira, Natália Carli [UNESP]; Martins, Lucas Michelão [UNESP]; Bueno, Cristina de Freitas [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP] (Wiley, 2024)
Reduced graphene oxide (rGO) and tin dioxide (SnO2) form composites in a wide range of SnO2/rGO proportions, which are deposited as thin films on borosilicate glass and silica substrates. The rGO proportion affects the SnO2 optical properties and the sample surface, as observed by optical transmittance and confocal and scanning electron microscopies images, mainly for high proportion of rGO. For low proportion, the presence of small surface islands may contribute to optical confinement. The evaluated bandgap is basically from the SnO2 matrix unless the presence of rGO affects the optical absorption edge. Monochromatic ultraviolet light from a He–Cd laser (325 nm) irradiating on the composite film increases the conductivity, giving rise to the phenomenon of persistent photoconductivity (PPC), even very close to room temperature. Modeling by considering mainly the SnO2/rGO interface barrier for electron transport, yield an interface energy barrier of 250 meV. The strong response to ultraviolet light and the phenomenon of PPC indicates potential application in amplifiers, which could be adjusted by doping with rare-earth ions, such as Er3+ in the SnO2 matrix.
Keywords: Composite; Reduced graphene oxide; Thin films; Tin dioxide